Effect of Surfosept and Deconex® 53 Disinfectant Agents on the Accuracy and Dimensional Stability of Panasil Dental Impression Materials: An Experimental Study. (21st October 2021) - Alam, Mostafa; Amini, Parviz; Ghaffarpasand, Arash; Dalooei, Nasim Khajeh; Hadi, Alireza; Abbasi, Kamyar
Abstract : Aim and Objective . Impression materials and stone casts are the main sources of cross-contamination and transmission of dental infections between dental offices and laboratories. Both Surfosept (alcohol-based) and Deconex® (quaternary ammonium compound) are biocompatible solutions that have superior antimicrobial properties against bacteria, fungi, and viral envelope. Considering the influence of disinfection substances on the dimensions of impression materials, this study aimed to compare the effect of Surfosept and Deconex® 53 on the accuracy and dimensional stability of the Panasil® dental addition silicone material. Materials and Methods . This in vitro study was performed on 30 dental casts. The samples were divided into one control group and two experimental groups to be disinfected with Surfosept (1%) and Deconex® 53 (2%) using a sequential sampling method (10 per group). The impressions in the experimental groups (i.e., Surfosept and Deconex® 53) were rinsed and dried; then, the disinfectant was sprayed on the impressions and remained for 30 seconds before pouring with stone. In the control group, the impressions were only rinsed and dried and were poured in 10 minutes. Cast dimensions were measured by a profile projector device, and the mean values obtained from the experimental groups were compared with those of the control group. Results . There were no significant differences among the groups regarding the height of the resulting dies without undercut (P = 0.62 ). Moreover, there was no significant difference among the groups regarding the distance between the two dies (P = 0.77 ). However, the diameter of the dies with undercut and without undercut was different significantly among the control and experimental groups (P < 0.005 ). Conclusion . In general, no significant difference was encountered between dimensional stability and accuracy of the dental impressions using Surfosept and Deconex® 53 in this study.